IMPLEMENTASI PERATURAN BUPATI NOMOR 30 TAHUN 2019 TENTANG ROAD MAP REFORMASI BIROKRASI PEMERINTAH KABUPATEN PONOROGO TAHUN 2019-2021 DI DINAS KOMUNIKASI INFORMATIKA DAN STATISTIK KABUPATEN PONOROGO - Kusuma Dewi, Dian Indriasari (JI@P, 2021)
The lack of an active role in implementing policies, lack of human resources and budget, as well as the availability of facilities and infrastructure were the causes of the inadequate implementation of bureaucratic reform in the Department of Communication, Informatics and Statistics, Ponorogo Regency. However, overall the implementation of bureaucratic reform has been going well. It only needs an increase and development of the quality and quantity of human resources. In addition, the availability of a budget and improvement of facilities and infrastructure to support the realization of the goals and objectives of bureaucratic reform.